CONCEPTUAL STUDY OF YUSHA (SOUPS) AS PATHYA AHARA KALPANA W.S.R. MUDGA YUSHA - Marwaha Mannat; Chugh Deepa (International Journal of Applied Ayurved Research, 2017)
Irregular life style, non-observance of Ritucharya, unwholesome food, wrong and un thoughtful habits of Ahara, Vihara leads to problems like Agnimandya (decreased digestive power), Ajirna (Indigestion) etc. Kritta Mudga Yusha (soup) is one of the best Ahara Kalpana which can be used in patients as well as healthy persons. Dravyas in Shami Dhanya Varga (Dicotyledonous group) are used to make Yusha. Agnimandya prevalent in Varsha and Vasant Ritu dealt with Yusha. General Method of preparation of Yusha, its types, its dose, seasonal consideration along with properties of different types of Yusha’s mentioned by Acharya Charaka, Sushruta and Kashyapa are discussed. Yushas are extensively used by the Acharyas in various diseases viz, Grahni, Gulma, Kushtha, Rakttapitta, Atisara, Vatavyadhi etc. Yushas are simple to make, ingredients are easily available worldwide. It is palatable, good in taste, color and smell. A preventive, promotive and curative effect of Yusha further confirms it as a healthy diet.